India's foreign policy - Ghosh, Anjali (Always learning., 2009)
In this volume, scholars specializing in different dimensions of foreign-policy analysis examine the dynamics of India's international relations. The volume reviews the economic growth that has propelled it to the status of a globally recognized power, and examines its nuclear policy and maritime strategy as a register of its present capabilities and future aspirations. The news media, often neglected in the study of international politics, are studied as an important index to-and catalysis for-the formulation of government policies. The volume also comprehensively analyses India's bilateral and multilateral relations, their influence on the stability of the subcontinent, their bearing on the country's international presence, and their relevance for its political ambitions.